(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, based on the generalized Gronwall inequality and the method of steps, an approach to the finite-time stability of nonlinear fractional order systems with a constant delay is proposed. A sufficient condition for finite-time stability of considered systems is presented. Compared with the finite-time stability criteria in the existing literature, our results are less conservative. Two examples are given to illustrate the effectiveness of the proposed theorem.